Naskah Melayu dengan Nama dan Tokoh Perempuan - Dewaki Kramadibrata (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2007)
This paper discussed Malay manuscripts which titled with womens' name and they also conduct as the heroine. The heroine, for example Siti Zawiyah and Siti l lasanah, were described as a beautiful lady, kind hearted, and very obedient to God. Meanwhile, Siti Zuhrah (she disguised as a man) was described as an ideal llcro.